Răspuns :
Notăm cu a,b numerele
a+b=361
a-b=25⇒a=b+25
Acum înlocuim în sumă a=b+25
b+25+b=361
2b+25=361
2b=361-25
2b=336
b=336:2
b=168
Acum înlocuim a=b+25⇒a=168+25=193
Numerele sunt 193 și 168
a+b=361
a-b=25⇒a=b+25
Acum înlocuim în sumă a=b+25
b+25+b=361
2b+25=361
2b=361-25
2b=336
b=336:2
b=168
Acum înlocuim a=b+25⇒a=168+25=193
Numerele sunt 193 și 168
A+B=361
A-B=25=>A=B+25
A+B=361/-25
B+B=336
336:2=168 este B
168+25= 193este A
A-B=25=>A=B+25
A+B=361/-25
B+B=336
336:2=168 este B
168+25= 193este A